Distribution of six phenolic acids and soil nutrient relationships during litter decomposition in Rhododendron forests - Zhao, Yumeng; Lin, Jian; Quan, Wenxuan; Li, Chaochan (Frontiers in Forests and Global Change, 2023)
Litter decomposition is an essential process in nutrient cycling in terrestrial ecosystems. Phenolic acids have an allelopathic effect on the natural regeneration of rhododendron forests, which was recently observed in rhododendron forests in Southwest China. We investigated the distribution of phenolic acids and their relationship with soil nutrients during litter decomposition to provide a reference for the subsequent artificial management of rhododendron forests. High-performance liquid chromatography (HPLC) was used to analyze the contents of six phenolic acids in the litter layer, humus layer, and soil layer during litter decomposition. During the first three months, the rapid decomposition of the litter from two early-flowering rhododendron species released large amounts of phenolic acids, and the lower litter layer decomposed rapidly. In addition, the total phenolic acid content in the litter decreased by 257.60 μg/g (Rhododendron siderophyllum) and 53.12 μg/g (Rhododendron annae) in the first three months. During subsequent litter decomposition, the protocatechuic acid content in the litters of Rhododendron siderophyllum ranged from 20.15 μg/g to 39.12 μg/g, and the ferulic acid content was 10.70 μg/g to 33.79 μg/g. The protocatechuic acid and ferulic acid contents in the litter of Rhododendron annae were in the ranges of 10.88-19.68 μg/g and 10.75-18.00 μg/g, respectively. The contents of these two phenolic acids and the trend of decomposition were different from those of gallic acid, chlorogenic acid, caffeic acid and syringic acid. The distribution of phenolic acids was influenced by soil organic matter (SOM), soil ammonium nitrogen (NH4+), soil nitrate nitrogen (NO3-) and soil available phosphorus (AP). The results indicate seasonal variations in phenolic acid release during litter decomposition. The amount of phenolic acid in the litter decreased after 18 months of decomposition, but it returned to the previous level in the soil and the humus after different trends. More research into the metabolism of phenolic acids is needed.